Heterosis for grain yield contributing traits in pearl millet (Pennisetum glaucum) - SINGH, JOGENDRA; SHARMA, VIVEK; SHARMA, L D; KUMAR SHARMA, SHRAVAN (The Indian Journal of Agricultural Sciences, 2022)
The general expectation of the pearl millet farmers is mainly focused on level of superiority of newly released hybrids than the local standard hybrids, which is grown widely. Hence, the standard check RHB-173, RHB-177 and MPMH-17 were used as standard hybrid. The hybrid namely RMS-7 × RIB-3135-18 expressed highest significant standard heterotic value for grain yield per plant and fourassociated traits out of nine studied traits including dry fodder yield per plot also showed positive significant standard heterosis. Similarly, another hybrid namely RMS-7 × RIB-16296 showed highest significant standard heterosis for dry fodder yield per plot. The showed cross combination, viz. ICMA-00444 × RIB-16S/110, ICMA-00111 × RIB-494, ICMA-00444 × RIB-16296 and ICMA-00444 × RIB-16328 were good for other studied traits. At the end, among 100 hybrids studied, one hybrid, viz. RMS-7 × RIB-3135-18 was selected as best cross since, it expressed high significant standard heterosis over best check for many of the traits including grain yield and dryfodder yield and may have potential to replace old cultivar in the future.